Plaque quantitiation through protein measurement - Smit, A. M.; Cleaton-Jones, P. E.; Boardman, M. E. (My University, 1992)
This study was undertaken to establish whether the quantitation of dental plaque protein by a dye-binding method (Coomassie G-250) may be used as an index of the amount of dental plaque sampled. Ten sites were sampled in 34 children on 5 occasions at 4 month intervals. The mean protein concentration in 1391 plaque samples was 6.9 +/- 4.1 micrograms (micrograms) (mean +/- standard deviation). A three-way analysis of variance showed that the plaque protein concentration was similar at the different sampling sites in the same child (p = 0.14), but statistically significant differences were observed with respect to time of sampling (F = 36.24; p = 0.0001) and individual sampled (F = 5.69; p = 0.0001). These observations indicate that plaque bacterial counts may be expressed as units of protein concentration and this method may be useful to relate the number of viable bacteria to an estimate of the amount of plaque collected. This ratio allows standardisation for any variation in the amount of plaque collected.
PK
Keywords: Bacterial Proteins/analysis; Dental Plaque/chemistry; Dental Plaque/microbiology